O40-1 Risk of hypersensitivity pneumonitis and other interstitial lung diseases among pigeon breeders. (1st September 2016) - Cramer, Christine; Schlünssen, Vivi; Bendstrup, Elisabeth; Stokholm, Zara Ann; Vestergaard, Jesper Medom; Frydenberg, Morten; Kolstad, Henrik Albert
Abstract : The objective of this study was to determine the risk of hypersensitivity pneumonitis (HP) and other interstitial lung diseases (ILD) among pigeon breeders. This is a retrospective follow-up study from 1980 to 2013 of 6920 pigeon breeders identified in the records of the Danish Racing Pigeon Association. They were compared with 276, 800 individually matched referents randomly drawn from the Danish population. Hospital based diagnoses of HP and other ILD were identified in the National Patient Registry 1977–2013. Stratified Cox regression analyses estimated the hazard ratios (HR) of HP and other ILD adjusted for occupation, residence, and redeemed prescription of medication with ILD as a possible side-effect. Subjects were censored at death, emigration, or a diagnosis of connective tissue disease. The overall incidence rate of ILD was 77.4 per 100, 000 person years among the pigeon breeders and 50.0 per 100, 000 person years among the referents. This difference corresponded to an adjusted HR of 1.56 (95% CI: 1.26–1.94). The adjusted HR of HP and other ILD for pigeon breeders were 14.36 (95% CI: 8.10–25.44) and 1.33 (95% CI: 1.05–1.69). Higher risk estimates for overall ILD and HP were observed among the subset of pigeon breeders who were followed since first enrolment into the pigeon association and thus with a complete pigeon breeder history. To conclude, this study shows an increased risk of ILD among pigeon breeders compared with the referent population. Protective measures are recommended even though ILD leading to hospital contact remains rare among pigeon breeders.